Spontaneous dissociation during functional MRI experiments - Michal, Matthias; Röder, Christian; Mayer, Jutta; Lengler, Ulrike; Krakow, Karsten (Journal of psychiatric research, 2007)
It is assumed that the procedures of functional magnetic resonance imaging (fMRI) are able to provoke significant dissociative responses. Trait and state dissociation of 32 healthy subjects undergoing fMRI have been recorded. At least one-third of the subjects showed dissociative responses of very large effect size ( d = 4.10). The contributing causal factors for that dissociative response could not yet identified clearly. Considering the impact of dissociation on mental functions, we recommend controlling subjects undergoing fMRI studies for dissociative responses. Further studies on the actual phenomenological experience of subjects undergoing fMRI procedures are warranted.